Peran Pendidikan Agama Kristen Dalam Mengatasi Tantangan Kesehatan Mental Pada Lansia - Trifosa, Florence; Herman, Samuel (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2025)
This research discusses the role of Christian religious education in addressing mental health challenges among the elderly. The aim of this study is to enhance the mental health of the elderly through the implementation of Christian religious education as a solid foundation. The method used in this research is qualitative research with a descriptive analysis method. Attention to the elderly is necessary to improve the quality of life for them, as there are many issues that can lead to depression and feelings of hopelessness among the elderly, especially considering that during old age, they often receive less specialized attention. Mental health needs to be a focus within families to ensure that the elderly can experience a happy quality of life in their later years. In old age, the transition from the productive phase of life, which is typically occupied with work and various activities, can have a significant impact, especially as the range of activities that can be undertaken decreases. This decline in activity is often accompanied by a reduction in income, which can limit their ability to do what they desire. Christian religious education for the elderly should continue in a character development approach to address various mental health disorders, both physically and spiritually.